A Novel High Performance Characteristic Resistance MPPT Algorithm for Photovoltaic Systems. (2020) - Shanifa Beevi, S.; Mathew, Johnson; Vincent, G.
Abstract: This paper proposes a novel high performance characteristic resistance MPPT algorithm for photovoltaic systems under rapidly changing environmental conditions. The methodology is based on the comparison of instantaneous resistance with characteristic resistance of the PV module corresponding to the prevailing climatic conditions. The characteristic resistanceof a PV module is the outputresistance at its maximum power point. Compared to conventional MPPT techniques, this algorithm offers a better performance in terms of start-up, steady-state and transient characteristics for all climatic conditions. Additionally, this algorithm fully eliminates the problem of drift. This technique is also simpler than conventional MPPT techniques. This proposal has been validated by experimental studies under suddenly changing climatic conditions.